NCOG-48. LONGITUDINAL ASSESSMENT OF SUBJECTIVE COGNITIVE FUNCTION IN A BRAIN TUMOR SAMPLE: IMPROVED CORRESPONDENCE WITH NEUROPSYCHOLOGICAL PERFORMANCE OVER TIME. (12th November 2021) - Gardner, Melissa; Zarrella, Giuliana; Dietrich, Jorg; Parsons, Michael
Abstract: INTRODUCTION: Estimates of subjective cognitive function (SCF) generally show minimal correlation with objective measures of neurocognitive function (NCF). Our group recently validated a new metric of SCF in neuro-oncology patients, creating the Cognitive Index of the Functional Assessment of Cancer Therapy-Brain (FACT-Br-CI). This study examines whether brain tumor (BT) patients evaluated on more than one occasion show improved relationship between SCF and NCF. We hypothesized that change scores in SCF and NCF across evaluation would be more highly correlated than SCF and NCF at either timepoint. METHODS: A retrospective study of BT patients who completed two neuropsychological evaluations (baseline, follow-up) was conducted. NCF was measured by the clinical trial battery composite (CTBC), a mean of 6 commonly used neuropsychological test scores. SCF was measured by the FACT-Br-CI. Mood/Anxiety were measured by the Beck scales (BAI/BDI-II). Change over time on each metric was evaluated with paired t-test. Correlational analyses evaluated relationships between NCF, SCF, and mood within and between time points. RESULTS: Twenty-nine patients (16 female; mean age=54.6y; mean education=15.5y) completed all CTBC measures and FACT-Br-CI, 28 of whom completed and BDI and/or BAI. On group analyses, there were no significant differences between baseline and follow-up on CTBC (t=-.53;p=ns) or FACT-Br-CI (t=-.98;p=ns). Correlations between CTBC and FACT-Br-CI were nonsignificant at baseline (r=.24;p=ns), but significant at follow-up (r=.56;p=0.002). Change scores over time were unrelated (r=-.104;p=ns). Similar to previous studies, the FACT-BR-CI correlated with the BDI-II at baseline (r=-.38;p=0.04) and follow-up (r=-.59;p< 0.001) and with the BAI at follow-up (r=-.44;p=0.02). CONCLUSION: In this small group of brain tumor patients seen for repeated neuropsychological evaluations, we found that agreement between SCF and NCF was much higher on their second than initial evaluation. These findings suggest that patients may develop enhanced awareness of their cognitive function from an initial evaluation that persists over time.